Dollars, “free trade,” and migration: the combined forces of alienation in postwar El Salvador - Garni, Alisa M.; Weyher, L. Frank (My University, 2013)
Driven by new conditions of desperation and alienation, mass migration in postwar El Salvador has continued unabated. While this migration could be seen as a way of “opting out” of on-going class struggle, we argue that it instead represents a critical dissipation of class relations and struggle. In the postwar context, the ruling class and the Salvadoran state now seek to capitalize upon the alienation of its own people and responses to that alienation – i.e., upon migration and the remittances it generates. The ruling class has ensured its economic domination regardless of who controls the state. Seeking to legitimize and maximize seizures of citizens’ income as it flows across borders as a matter of “economic” and “development” policy, the ruling class has depleted the productive base through which class struggle would ordinarily occur, creating new forces of alienation in El Salvador and extending the need for many Salvadorans to migrate.
Keywords: Alienation; Migration; Dollarization; Class relations; El Salvador